2020
DOI: 10.3390/nu12113418
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Characteristics, Dietary, and Nutritional Intakes of French Elderly Community Dwellers According to Their Dairy Product Consumption: Data from the Three-City Cohort

Abstract: Few data are available regarding dietary habits of the elderly, especially about dairy products (DPs) (total DP and milk, fresh DP, and cheese), whereas these are part of healthy habits. The aim was to describe the socio-demographic characteristics, food, and nutritional intakes of elderly DP consumers. The sample consisted of 1584 participants from the Three-City-Bordeaux cohort (France), who answered a food frequency questionnaire and a 24-h dietary recall. Socio-demographic characteristics, practice of phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Therefore, despite the higher consumption frequency, this intake might have been below what is recommended and therefore affected our results. In fact, in a recent analysis of the 3C-study participants describing their DP intake at baseline, it was observed that participants with the highest frequency of total DP per day consumed lower than the recommended intakes [ 31 ]. These results were in line with a previous national report where it was observed that 64% of participants aged 55 to 79 years old reported consumption below recommendations [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, despite the higher consumption frequency, this intake might have been below what is recommended and therefore affected our results. In fact, in a recent analysis of the 3C-study participants describing their DP intake at baseline, it was observed that participants with the highest frequency of total DP per day consumed lower than the recommended intakes [ 31 ]. These results were in line with a previous national report where it was observed that 64% of participants aged 55 to 79 years old reported consumption below recommendations [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results were in line with a previous national report where it was observed that 64% of participants aged 55 to 79 years old reported consumption below recommendations [ 47 ]. Second, in the 3C-study, total DP consumption and its sub-types have been previously shown to be associated with different eating patterns [ 31 ]. Although we have adjusted for diet quality in our analyses, we cannot exclude the possibility of some residual confounding that has led to an absence of significance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations